2020
DOI: 10.1007/s43440-020-00109-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced peripheral neuropathy: part 1—current state of knowledge and perspectives for pharmacotherapy

Abstract: Background Despite the increasing knowledge of the etiology of neuropathic pain, this type of chronic pain is resistant to available analgesics in approximately 50% of patients and therefore is continuously a subject of considerable interest for physiologists, neurologists, medicinal chemists, pharmacologists and others searching for more effective treatment options for this debilitating condition. Materials and methods The present review article is the first of the two articles focused on chemotherapy-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 183 publications
(301 reference statements)
0
60
0
Order By: Relevance
“…At present, bortezomib is often used for chemotherapy of multiple myeloma and mantle cell lymphoma. However, bortezomib-induced peripheral neuropathy (BIPN), characterized by numbness and painful paresthesia, remains one of the most troubling adverse reactions [ 4 , 5 , 6 , 7 , 8 ]. According to clinical practice guidelines released by the American Society of Clinical Oncology (ASCO) in 2014, there are no highly recommended therapies for the prevention or treatment of existing chemotherapy-induced peripheral neuropathy (CIPN), including BIPN [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, bortezomib is often used for chemotherapy of multiple myeloma and mantle cell lymphoma. However, bortezomib-induced peripheral neuropathy (BIPN), characterized by numbness and painful paresthesia, remains one of the most troubling adverse reactions [ 4 , 5 , 6 , 7 , 8 ]. According to clinical practice guidelines released by the American Society of Clinical Oncology (ASCO) in 2014, there are no highly recommended therapies for the prevention or treatment of existing chemotherapy-induced peripheral neuropathy (CIPN), including BIPN [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] We aimed to test compounds 6 and 7 during both these phases of CIPN to elucidate potential mechanisms underlying in vivo activity of these compounds. Acute neuropathy caused by oxaliplatin results from a transient impairment of ion channels and nerve hyperexcitability due to VGSC activation [ 30–32 ] and VGCC activation. [ 33 ] During this acute phase, neurotoxicity induced by oxaliplatin is perceived to be due to the accumulation of its metabolite, oxalate, which acts as a calcium chelator, indirectly altering the kinetics of calcium‐sensitive VGSCs.…”
Section: Resultsmentioning
confidence: 99%
“…This dose was previously tested in the oxaliplatin-induced neuropathic pain model and although it attenuated tactile allodynia in neuropathic mice, it did not reduce cold allodynia, or cold hyperalgesia [ 13 ]. The efficacy of pregabalin in reducing cold hypersensitivity is still a subject of debate and so far both preclinical and clinical studies have given many inconclusive data [ 1 , 19 , 20 , 21 , 22 , 23 , 24 ]. In our present study we observed that pregabalin-treated mice showed preference towards a colder plate of the two used and this effect was observed at temperatures 0–45 °C.…”
Section: Discussionmentioning
confidence: 99%
“…So far, many pharmacological strategies to treat cold-exacerbated pain have failed to provide analgesia in oxaliplatin-treated animals [ 1 , 13 , 22 , 25 , 26 ] and humans [ 1 , 26 , 27 , 28 ]. On the other hand, it is also likely that (1) the in vivo methods used at the preclinical stage (i.e., behavioral tests) might not be sensitive enough to detect analgesic active compounds, or (2) the parameters used to assess analgesic activity (i.e., temperatures at which chemical compounds were tested) are suboptimal.…”
Section: Discussionmentioning
confidence: 99%